Evaluation as applied research of social policy - Євдокимова, І. А. (SOCIOPROSTIR: the Interdisciplinary Online Collection of Scientific Works on Sociology and Social Work, 2015)
The review of theory and methodology of evaluation as a type of applied researches of social policy and some trends of evaluation development in the world and in Ukraine are presented in the article. A thesis that active development of methodology and practice of evaluation of social policy in different countries is grounded on the demand to have the information about results and process of social policy. It is also argued that in becoming of evaluation researches the trend of modern science is represented that consists in forming of interdisciplinary researches. The tendencies in developing of social policy evaluation in Ukraine are distinguished in the article. It is stressed that evaluation of social policy in modern Ukraine after appearance of certain markers of hope on development appeared before the risk of oblivion.